Heat-conducting powder tabletting method and obtained sheet
By using a mixed solution of binder and lubricant in the monene thermally conductive powder for tableting, the problem of difficult molding of the monene thermally conductive powder and inaccurate thermal conductivity detection during tableting is solved, and high compression is achieved The production of sheets improves the accuracy of thermal conductivity measurement and data reliability.
Patent Information
- Application Number
- CN202411461564.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-17
AI Technical Summary
During the tableting process, the monene thermal conduction powder is difficult to form a sheet due to the large thermal resistance of the heat transfer interface between particles, the small loose density, the rough surface and the low compressibility. In the prior art, the sample sheet is easy to be formed when the particle size is micron. Loose, unable to accurately detect thermal conductivity.
After mixing a mixed solution of binder and lubricant with the thermally conductive powder, the pressure of 60 to 100MPa is applied through an automatic tablet press, combined with the drying step to improve molding consistency and uniformity, and avoid uneven adhesive distribution. and difficult to demold.
It significantly improves the friction performance between powder particles, improves the uniformity of tablet forming and the firmness of the sample, simplifies the mold release process, and enhances the accuracy of thermal conductivity measurement and data reliability.
Smart Images

Figure CN119144301A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material preparation, and in particular relates to a method for tableting a thermally conductive powder and a sheet material prepared by the method. Background Art
[0002] With the rapid development of integrated circuit technology, the integration and assembly density of electronic components are constantly improving, and electronic components are gradually developing in the direction of miniaturization, refinement and lightness. Heat dissipation design is the key to reducing the size of devices. Therefore, finding an effective heat dissipation method has become a key research task at present. The key to solving this problem is the heat dissipation of electronic components, which directly determines the operating speed, reliability, stability and service life of electronic products. At present, the most widely used method is to fill materials with high thermal conductivity between electronic devices and equipment to improve the overall heat dissipation efficiency of the system. Traditional thermal conductive powders such as aluminum oxide, aluminum nitride, magnesium oxide, silicon carbide, etc. are economical and applicable fillers for insulating thermal interface materials due to their low price, large filling amount and stable properties. In order to improve its thermal conductivity, graphene, a new nanomaterial with a single-layer sheet structure composed of carbon atoms, has an ultra-high carrier mobility (~105cm 2 ·V -1 ·s -1 ), ultra-high thermal conductivity (~5000W·m -1 ·K -1 ) and ultra-high mechanical strength (~1.1TPa), etc. As a new type of composite material system, the monene thermal conductive powder derived from graphene is prepared by the high-temperature chemical vapor deposition method (CVD) to achieve the stable composite of traditional thermal conductive powder and graphene. The high-performance graphene skin can greatly improve the thermal conductivity of the thermal conductive powder.
[0003] However, when testing the thermal conductivity of monene thermal conductive powder, the density difference of conventional powder supports through natural filling and compaction leads to large thermal resistance of the heat transfer interface between particles, and the test is inaccurate or impossible to test. Therefore, the monene thermal conductive powder needs to be pre-processed and pressed into tablets, but due to the low bulk density between particles, rough particle surface, low compressibility, large porosity and poor fluidity, it is easy to produce "arching" phenomenon or form rat holes when pressure is applied and stacked, which increases the difference in tablet weight and is not conducive to the material filling of tablets. As a result, the powder loosens, cracks, sticks, and disintegrates after pressing, making it difficult to remove, and it cannot be formed into tablets, which seriously restricts the accurate test of thermal conductivity.
[0004] Prior art CN105047974A discloses a tableting method for nano-viscous powders, which stipulates that the powders are formed at a pressure of 60 to 100 MPa, and the sample forming and demolding are facilitated by adding barrier powder and paper. However, when this technology is applied to monene thermal conductive powders with a particle size range of micrometers, the samples after direct tableting tend to be loose. It is difficult to form. In addition, CN113387710A discloses a binder-free powder granulation and tableting method, which uses the method of mixing the powders evenly without adding a binder, and then granulating and tableting them through screening and temperature sintering. However, after calcining the monene thermal conductive powder, it may cause secondary modification of the material or decomposition of the surface carbon material graphene, which directly affects its thermal performance detection.
[0005] Therefore, there is an urgent need to find a convenient and feasible powder tableting method to solve the problems of loose flakes, cracked flakes and excessive weight difference in traditional powder tableting, and at the same time enable the thermal performance parameters of monene thermal conductive powder to be intuitively detected. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for tableting a thermally conductive powder and a sheet prepared by the method.
[0007] The invention provides a method for tabletting a heat-conducting powder, comprising: dispersing an appropriate amount of a binder and a lubricant in a dispersant to form a mixed solution; and tabletting the heat-conducting powder and the mixed solution.
[0008] According to an embodiment of the present invention, the total mass fraction of the binder and the lubricant in the mixed solution is 2% to 8%, and the mass ratio of the binder to the lubricant is 4-6:4-6.
[0009] According to another embodiment of the present invention, the mass ratio of the thermally conductive powder to the mixed solution is 4-10:0.5-1.2.
[0010] According to another embodiment of the present invention, the thermally conductive powder is one or more of alumina powder, monene alumina powder, magnesium oxide powder, monene magnesium oxide powder, aluminum nitride powder, monene aluminum nitride powder, silicon carbide powder, and monene silicon carbide powder.
[0011] According to another embodiment of the present invention, the particle shape of the thermally conductive powder is one or more of spherical, quasi-spherical, ellipsoidal, and irregular block, and the particle size of the thermally conductive powder is in the range of 100 nm to 120 μm.
[0012] According to another embodiment of the present invention, the binder is one or more of polyvinyl alcohol, polyvinyl butyral, hydroxypropyl methylcellulose, hydroxyethyl cellulose, acrylic acid, and pinene alcohol.
[0013] According to another embodiment of the present invention, the lubricant is one or more of polyvinyl pyrrolidone, polyethylene glycol, sodium polyacrylate, and polyoxyethylene.
[0014] According to another embodiment of the present invention, the dispersant is an ethanol solution with a concentration of 40-80% or a methanol solution with a concentration of 40-80%.
[0015] According to another embodiment of the present invention, the tableting is completed by an automatic tablet press, the applied pressure is 60 to 100 MPa, and the pressing time is 20 to 60 seconds.
[0016] According to another embodiment of the present invention, the tableting further includes a drying step, wherein the drying step comprises baking at a drying temperature of 40 to 60° C. for 5 to 30 minutes and then naturally drying for 8 to 18 hours.
[0017] The present invention also provides a thermally conductive powder sheet obtained by the method.
[0018] The thermally conductive powder tableting method of the present invention significantly improves the friction performance between powder particles by adding mixed reagents (binder and lubricant) compared to adding only a binder, making it easier to take out the sample after tableting, and significantly improving the consistency and uniformity of the sample during the tableting process of the powder. The key problems of poor fluidity between particles, easy dispersion, stratification and cracking, and sticking and disintegration of thermally conductive powder during tableting are solved, and the phenomena of uneven distribution and demolding difficulties that may occur when adding a binder alone are avoided. At the same time, the thermally conductive powder tableting method of the present invention can achieve tableting while using a smaller amount of reagents, thereby further improving the accuracy of thermal conductivity measurement of thermal conductive powder. The sample prepared by the present invention has high compressibility, is strong and not easy to break, has a simple process, is easy to demold, and can achieve rapid drying. When the sheet prepared by the method of the present invention is used for thermal performance analysis such as thermal conductivity, the test result has a high repetition rate and a small error, thereby improving the reliability of the overall data. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the method for pressing the monene alumina thermally conductive powder into tablets in Example 1.
[0020] Figure 2 It is a schematic diagram of the method for pressing the monene aluminum nitride thermal conductive powder into tablets in Example 2.
[0021] Figure 3 It is a schematic diagram of the method for tabletting the monene magnesium oxide thermal conductive powder of Example 3.
[0022] Figure 4 It is a schematic diagram of the method for pressing the monene silicon carbide thermal conductive powder into tablets in Example 4. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with specific implementation modes.
[0024] The tableting method of the thermally conductive powder of the present invention comprises: dispersing an appropriate amount of a binder and a lubricant in a dispersant to form a mixed solution; and tableting the thermally conductive powder and the mixed solution. The powder tableting method of the present invention solves the key problems of poor fluidity between particles of the thermally conductive powder, easy dispersion, stratification and cracking, and sticking and disintegration during tableting by adding mixed reagents, binders and lubricants, and also avoids the uneven distribution and demolding difficulties that may occur when a binder is added alone. The lubricant in the mixed reagent improves the friction performance between the powder particles, making it easier to remove the sample after tableting, and significantly improves the consistency and uniformity of the sample during the tableting process of the powder. At the same time, the tableting method of the present invention can achieve uniform tableting using a smaller amount of reagents than using only a binder, thereby further improving the measurement accuracy of parameters such as the thermal conductivity of the thermally conductive powder.
[0025] In an optional embodiment, the total mass fraction of the binder and the lubricant in the mixed solution is 2% to 8%. The mass of the binder and the lubricant in the mixed solution can be selected according to the influence of the binder and the lubricant on the tableting performance. In general, the mass ratio of the binder to the lubricant is 4 to 6:4 to 6.
[0026] In an optional embodiment, the mass ratio of the thermally conductive powder to the mixed solution is 4-10:0.5-1.2.
[0027] In an optional embodiment, the tableting method of the present invention is suitable for thermally conductive powders with a particle size of 100nm to 120μm, such as but not limited to one or more of alumina powder, monene alumina powder, aluminum nitride powder, monene aluminum nitride powder, silicon carbide powder, monene silicon carbide powder, etc. Among them, monene alumina powder, monene aluminum nitride powder, magnesium oxide powder, monene magnesium oxide powder, and monene silicon carbide powder can all become monene thermally conductive powders. The monene thermally conductive powder in this patent refers to a composite powder formed by directly growing graphene on the surface of the thermally conductive powder by vapor deposition.
[0028] In an optional embodiment, the shape of the thermally conductive powder particles can be one or more of spherical, quasi-spherical, ellipsoidal, and irregular blocks. The particle size of the thermally conductive powder ranges from 100 nm to 120 μm.
[0029] In an optional embodiment, the binder may be one or more of polyvinyl alcohol (PVA), polyvinyl butyral (PVB), hydroxypropyl methylcellulose (HPMC), hydroxyethyl cellulose (HEC), acrylic acid, and pinene alcohol.
[0030] In an optional embodiment, the lubricant may be one or more of polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), sodium polyacrylate (SP), and polyoxyethylene (POE).
[0031] In an optional embodiment, the dispersant may be an ethanol solution with a concentration of 40-80% or a methanol solution with a concentration of 40-80%.
[0032] In an optional embodiment, tableting is performed by an automatic tablet press, which reduces human interference, and has good consistency, good uniformity and high efficiency in tableting. The pressure applied during tableting is 60-100 MPa, and the pressing time is 20-60 seconds.
[0033] In an optional embodiment, a drying step is further included after tabletting, wherein the drying step is performed at a drying temperature of 40 to 60° C. for 5 to 30 minutes and then naturally dried for 8 to 18 hours.
[0034] The present invention also provides a thermally conductive powder sheet obtained by the above method. The sheet prepared by the method of the present invention has good uniformity, so when used for thermal performance analysis such as thermal conductivity, the test result has high repetition rate and small error, thereby improving the reliability of the test result.
[0035] The present invention is further described below by specific examples. However, these examples are merely exemplary and do not constitute any limitation to the scope of the present invention. In the following examples and comparative examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0036] Example 1
[0037] Combination Figure 1 The tabletting method is schematically shown in FIG. 1 , and this embodiment is described in detail below.
[0038] A 50% ethanol solution was used as a dispersant. Under stirring, equal masses of PVA and PVP were added to the dispersant. The temperature of the magnetic stirrer was adjusted to 105°C and heated on a magnetic stirring hot plate for 1.5 h until the solution was a uniform mixed solution. A mixed solution with a total mass fraction of PVA and PVP of 4% was prepared, and the mass ratio of PVA to PVP was 1:1.
[0039] The mixture was added to 0.08 parts by mass of the prepared mixed solution, and then added dropwise to 0.8 parts by mass of monene alumina powder (spherical or quasi-spherical) having an average particle size of 10 μm, and mixed evenly.
[0040] The evenly mixed monene alumina powder is filled into the three-petal mold of the automatic infrared tablet press, with a gasket placed on the top and bottom respectively. The powder is filled to the middle of the gasket, and the mold pressing shaft is used to press lightly to make the powder accumulate. Then, the powder is placed on the sample table of the automatic infrared machine, and the pressure is set to 100 MPa and the time is 30 seconds. The tableting and demolding are started.
[0041] Open the three-flap mold, take out the mold gasket above the sample, gently transfer it to the weighing paper, and use an infrared baking lamp to irradiate for 15 minutes until the sample is dry to obtain a dense and high-strength disc. The prepared discs were tested for performance. Using the hotdisk thermal constant analyzer and the transient plane heat source method, two parallel discs were fixed on the instrument probe for testing to obtain the thermal conductivity value. Five points were tested on the sample, and the test results are shown in Table 1.
[0042] Table 1
[0043]
[0044] Example 2
[0045] Combination Figure 2 The tabletting method is schematically shown in FIG. 1 , and this embodiment is described in detail below.
[0046] A mixed solution with a total mass concentration of PVA and PVP of 8% was prepared by using a 40% ethanol solution and equal masses of PVA and PVP in the same manner as in Example 1, and the mass ratio of PVA to PVP was 2:3.
[0047] 0.05 parts by mass of the prepared mixed solution was dropped into 1 part by mass of monene aluminum nitride powder (ellipsoid) having an average particle size of 3 μm and mixed evenly.
[0048] Tableting and testing were performed in the same manner as in Example 1. The test results are shown in Table 2.
[0049] Table 2
[0050]
[0051] Example 3
[0052] Combination Figure 3 The tabletting method is schematically shown in FIG. 1 , and this embodiment is described in detail below.
[0053] A mixed solution with a total mass concentration of PVA and PVP of 2% was prepared by using an 80% ethanol solution and equal masses of PVA and PVP in the same manner as in Example 1, and the mass ratio of PVA to PVP was 3:2.
[0054] 0.08 parts by mass of the prepared mixed solution was dropped into 0.4 parts by mass of monene magnesium oxide powder having an average particle size of 5 μm and mixed evenly.
[0055] Except that the pressure was set to 60 MPa, tableting and testing were carried out in the same manner as in Example 1. The test results are shown in Table 3.
[0056] Table 3
[0057]
[0058] Example 4
[0059] Combination Figure 4 The tabletting method is schematically shown in FIG. 1 , and this embodiment is described in detail below.
[0060] A mixed solution with a total mass concentration of PVA and PVP of 4% was prepared by using a 50% ethanol solution and equal masses of PVA and PVP in the same manner as in Example 1, and the mass ratio of PVA to PVP was 1:1.
[0061] 0.12 parts by mass of the prepared mixed solution was dropped into 0.8 parts by mass of silicon carbide powder (irregular blocks) having an average particle size of 5 μm and mixed evenly.
[0062] Except that the pressure was set to 80 MPa, tableting and testing were carried out in the same manner as in Example 1. The test results are shown in Table 4.
[0063] Table 4
[0064]
[0065] It can be seen from the test data in Tables 1-4 that the standard deviation of the thermal conductivity of the thermally conductive powder measured by the tableting method of the present invention is small, indicating that the sheet obtained by the tableting method of the present invention has a high repetition rate and a small error in the measurement of the thermal conductivity of the thermally conductive powder, thereby improving the reliability of the measurement data.
[0066] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for tabletting a thermally conductive powder, characterized in that: include: Dispersing appropriate amounts of binder and lubricant in a dispersant to form a mixed solution; The thermally conductive powder and the mixed solution are mixed and then pressed into tablets.
2. The thermally conductive powder tabletting method according to claim 1, characterized in that: The total mass fraction of the binder and the lubricant in the mixed solution is 2% to 8%, and the mass ratio of the binder to the lubricant is 4 to 6:4 to 6.
3. The thermally conductive powder tableting method according to claim 2, characterized in that: The mass ratio of the thermally conductive powder to the mixed solution is 4-10:0.5-1.
2.
4. The thermally conductive powder tabletting method according to claim 1, characterized in that: The thermally conductive powder is one or more of alumina powder, monene alumina powder, magnesium oxide powder, monene magnesium oxide powder, aluminum nitride powder, monene aluminum nitride powder, silicon carbide powder, and monene silicon carbide powder.
5. The thermally conductive powder tableting method according to claim 1, characterized in that: The particle shape of the thermally conductive powder is one or more of spherical, quasi-spherical, ellipsoidal, and irregular block, and the particle size of the thermally conductive powder is in the range of 100 nm to 120 μm.
6. The thermally conductive powder tableting method according to claim 1, characterized in that: The binder is one or more of polyvinyl alcohol, polyvinyl butyral, hydroxypropyl methylcellulose, hydroxyethyl cellulose, acrylic acid, and pinene alcohol; and / or The lubricant is one or more of polyvinyl pyrrolidone, polyethylene glycol, sodium polyacrylate, and polyoxyethylene.
7. The thermally conductive powder tableting method according to claim 1, characterized in that: The dispersant is an ethanol solution with a concentration of 40-80% or a methanol solution with a concentration of 40-80%.
8. The thermally conductive powder tableting method according to claim 1, characterized in that: The tableting is completed by an automatic tablet press, with an applied pressure of 60 to 100 MPa and a pressing time of 20 to 60 seconds.
9. The thermally conductive powder tableting method according to claim 1, characterized in that: The tabletting process further includes a drying step, wherein the drying step comprises baking at a drying temperature of 40 to 60° C. for 5 to 30 minutes and then naturally drying for 8 to 18 hours.
10. A thermally conductive powder sheet, characterized in that: Prepared by the thermally conductive powder tableting method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Tabletting and molding method for nano sticky powder
CN105047974A
Cited By
Copper ore sample preparation and detection method for X-ray fluorescence spectrum analysis
CN121027186A
